Biochemical Composition Variation among Southern Ethiopian Arabica Coffee (Coffea arabica L.) Genotypes - Meseret Degefa; Sentayehu Alamerew; Ali Mohammed; Adeba Gemechu (International Journal of Agronomy)
Coffee (Coffea arabica L.) provides several health benefits to users due to its strong medicinal and nutritional properties and caloric value. Green bean proximate composition diversity is unknown among the coffee genotypes now cultivated in southern Ethiopia. The study’s major goals are to determine the variability in green bean proximate composition among coffee genotypes and to see if there are any relationships between green bean proximate attributes. Therefore, a nutritional laboratory experiment was carried out at Jimma University College of Agriculture and Veterinary Medicine (JUCAVM). Using the augmented design, a total of 104 entries were examined, including 100 accessions from southern Ethiopia and four standard checks. Each accession had data on 07 proximate composition parameters of green beans. The presence of significant (P<0.05) differences among the examined accessions for most of the traits considered was revealed by analysis of variance, and a wide range of variation was detected for several traits, indicating that the coffee germplasm accessions have high genetic variability. According to the findings, coffee beans have crude protein (6.93 to 10.14%), total lipids (8.89 to 16.08%), crude ash (2.51–5.47%), crude fiber (6.79–22.25%), dry matter (89.08 to 91.63%), carbohydrate (40.65 to 59.38%), and caloric value (307.39–382.77 k/calories). One hundred four arabica coffee accessions were grouped into ten distinct groups by 20 (19.23%), 21 (20.19%), 39 (37.50%), 12 (11.54%), 04 (3.85%), 03 (2.88%), 02 (1.92%), 01 (0.96%), 01 (0.96%), and 01 (0.96%). The majority of intercluster distances were significantly varied, showing that diversity exists that can be utilized through selection and hybridization. Clusters III and X had the greatest intercluster distance (D2 = 344.16), followed by clusters II and X (D2 = 236.33), VII and X (D2 = 199.04), and clusters VI and I (D2 = 106.25). Clusters I and IV had the smallest intercluster distance (D2 = 10.09), followed by II and IV (D2 = 10.66), and I and VI (D2 = 11.03). The first three principal components with eigenvalues larger than one explained 71.84% of the overall variation. In general, genotypes differed in green bean proximate composition and might be used as gene sources to generate future green bean varieties with appropriate biochemical composition.